The relationship between inclusion climate and voice behaviors beyond social exchange obligation: The role of psychological needs satisfaction - Paolillo, A. (2021)
Several studies have identified a work environment that promotes inclusiveness as a significant predictor of affiliative organizational citizenship behavior or OCB (such as helping), whereas not much research has focused on inclusion and challenging OCB (i.e., voice). Moreover, no previous studies have explored the above-mentioned relationship in the light of self-determination theory (SDT), given that social exchange theory has traditionally been used as the main explanatory mechanism. Therefore, the aim of the present research was to test the mediating role of basic psychological needs satisfaction in the relationship between inclusion climate, promotive voice and prohibitive voice. Data were collected through self-report questionnaires administered to 246 employees of an international company operating in the service industry. Structural equation modelling was used to analyze the data utilizing R software. Results showed that satisfaction of the needs for autonomy, competence and relatedness partially mediated the relationship between inclusion climate and promotive and prohibitive voice, therefore supporting the idea that social exchange might not be the only determinant for employees to engage in voice behavior. Most importantly, those findings underline how a truly inclusive workplace needs to fulfil its employees’ basic needs of behaving volitionally, feeling effective and connecting meaningfully; this would motivatethe workers to voice their suggestions and concerns.